Interrogating marginalities across disciplinary boundaries
1 online resource
Keywords: "This volume adopts an inter-disciplinary approach to rethink the multiple dimensions of marginality - political, societal, economic, cultural, legal, spatial. It explores their new representations in colonial and postcolonial India. Departing from extant analyses of experiences of marginalization in diverse social groups, it proposes to problematize the conceptualization of marginality, focusing on its evolution through space and time. A relational position, marginality, it is argued, presupposes a confrontation with centrality or the 'mainstream' within a common discourse of knowledge and power. The volume emphasizes that the process of marginalization is not a 'marginal' phenomenon and draws attention to the historical processes which determine, establish and perpetuate the margins. The book reflects on varied aspects of evolving marginalities - structural, cultural and psychological - in South Asia in diverse temporal, spatial or societal contexts. It examines the discourses, institutional mechanisms and economic processes within which marginalities are located. This work will be an important read for scholars and researchers of history, anthropology, subaltern studies, exclusion studies, South Asian history, post-colonial studies, political studies, Indian history, cultural studies, and history, in general"--